2015
DOI: 10.1002/eat.22485
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole, a partial dopamine agonist to improve adolescent anorexia nervosa—A case series

Abstract: Anorexia nervosa (AN) is a severe and complex psychiatric disorder and no medication has been approved for its treatment. This case series in youth with severe, recurrent AN supports the hypothesis that dopamine receptor agonists could be helpful in supporting fear extinction during eating disorder focused psychotherapy and therefore support recovery from AN. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:529-533).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…A few case reports suggest that aripiprazole -a partial dopamine agonistmay also be effective in the treatment of AN [125][126][127]. In a chart review of 75 patients with AN who received either olanzapine or aripiprazole, aripiprazole showed the greatest effectiveness in reducing eating-related preoccupations and rituals with a large effect size [128].…”
Section: Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few case reports suggest that aripiprazole -a partial dopamine agonistmay also be effective in the treatment of AN [125][126][127]. In a chart review of 75 patients with AN who received either olanzapine or aripiprazole, aripiprazole showed the greatest effectiveness in reducing eating-related preoccupations and rituals with a large effect size [128].…”
Section: Antipsychoticsmentioning
confidence: 99%
“…In a chart review of 75 patients with AN who received either olanzapine or aripiprazole, aripiprazole showed the greatest effectiveness in reducing eating-related preoccupations and rituals with a large effect size [128]. In the literature [125][126][127], relatively small doses were used. For example, in a case series published by Trunko et al [125] patients received aripiprazole doses of between 5 and 15 mg/d.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…This could have relevance for anorexia nervosa treatment and improve psychotherapy outcomes in this disorder. Three case reports supported benefits from prescription of the partial dopamine D2 receptor agonist aripiprazole in adults and youth with the disorder (Aragona, 2007;Frank, 2016a;Trunko, Schwartz, Duvvuri, & Kaye, 2011). One retrospective study suggested that the combination of a serotonin reuptake inhibitor (SSRI) with an atypical antipsychotic might reduce anorexia nervosa-related cognitions but did not show benefits for weight gain (Marzola et al, 2015).…”
Section: A R I P Ip R a Z O L E I N A N O R E X Ia N E R V O S Amentioning
confidence: 99%
“…One case report in a sample of six patients with AN showed that a low dose of the dopamine agonist levodopa was helpful for weight gain in four patients, while the two non-responders maintained their weight [162]. Other evidence for dopamine agonists comes from case reports that suggest that the dopamine receptor partial agonist aripiprazole at a relatively low dose can reduce fear of weight gain and support AN treatment outcome [85, 84]. …”
Section: New Approaches To Medication Intervention In Anmentioning
confidence: 99%
“…In support of the low-dose approach is a study of AN that administered low-dose olanzapine to 13 patients and found that the medication showed indications supporting weight gain and reducing hyperactivity. Similarly, case reports of aripiprazole in AN suggest the use of low dosages [85]. Taking this small amount of information into consideration, it might be best to start medication below the typical dosage and slowly up-titrate, depending on clinical response.…”
Section: New Approaches To Medication Intervention In Anmentioning
confidence: 99%